MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYAH MELALUI MEDIA KARTU BERGAMBAR PADA ANAK USIA 4-5 TAHUN DI RA ASSAKINAH KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Nurhabibi Nurhabibi; Isjoni Isjoni; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to determine the ability to recognize letters hijaiyah improvement in children aged 4-5 years through the medium of picture cards in Ra Assakinah District Of Payung Sekaki Pekanbaru City. This study is the kind of research that uses classroom action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. The subjects were children aged 4-5 years in the RA Assakinah. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The results showed that the media picture cards can improve the ability to read letters hijaiyah in children aged 4-5 years. It can be seen from the increase in the average percentage hijaiyah ability to recognize letters in the first cycle of 54.83% which is the criterion begins to develop (MB) and an increase of 45.10% in the second cycle into 79.56 which is the criterion developing according to expectations (BSH). Thus, the beam cruissenere games can improve cognitive ability letters hijaiyah children aged 4-5 years in Ra Assakinah District Of Payung Sekaki Pekanbaru City.Keywords: Ability to Know Letter Hijaiyah, Media Picture Cards